2013
DOI: 10.1080/10106049.2013.827750
|View full text |Cite
|
Sign up to set email alerts
|

Statistical data fusion of multi-sensor AOD over the Continental United States

Abstract: This article illustrates two techniques for merging daily aerosol optical depth (AOD) measurements from satellite and ground-based data sources to achieve optimal data quality and spatial coverage. The first technique is a traditional Universal Kriging (UK) approach employed to predict AOD from multi-sensor aerosol products that are aggregated on a reference grid with AERONET as ground truth. The second technique is spatial statistical data fusion (SSDF); a method designed for massive satellite data interpolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Baker et al (2012) analyzed trace metals in wetlands constructed using petcoke and other consolidated waste sediments in the Alberta tar sands (Canada), founding high concentrations of Ni and V, attributed to petcoke, at levels that are toxic to local invertebrate species. Their results supported the findings of Puttaswamy et al (2014), who found high levels of Ni and V in leachates collected from shallow and deep lysimeters in the same region. Both lysimeters were buried in petcoke and covered in glacial till (deep lysimeter) or peat (shallow lysimeter), and the concentrations measured were toxic to freshwater species.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Baker et al (2012) analyzed trace metals in wetlands constructed using petcoke and other consolidated waste sediments in the Alberta tar sands (Canada), founding high concentrations of Ni and V, attributed to petcoke, at levels that are toxic to local invertebrate species. Their results supported the findings of Puttaswamy et al (2014), who found high levels of Ni and V in leachates collected from shallow and deep lysimeters in the same region. Both lysimeters were buried in petcoke and covered in glacial till (deep lysimeter) or peat (shallow lysimeter), and the concentrations measured were toxic to freshwater species.…”
Section: Introductionsupporting
confidence: 88%
“…Increase in the concentration of heavy metals in the aquatic environment due to petcoke leaching was also reported, with noteworthy effects to local aquatic species (Caruso et al 2015;Puttaswamy et al 2014). Baker et al (2012) analyzed trace metals in wetlands constructed using petcoke and other consolidated waste sediments in the Alberta tar sands (Canada), founding high concentrations of Ni and V, attributed to petcoke, at levels that are toxic to local invertebrate species.…”
Section: Introductionmentioning
confidence: 92%
“…To improve the spatial coverage of the MAIAC AOD data, linear regression between daily Terra AOD and Aqua AOD were used to predict missing AOD when only one of them was available (X. F. Hu, Waller, Lyapustin, Wang, Al-Hamdan, et al, 2014; Jinnagara Puttaswamy et al, 2014). Then AOD data from both satellite were averaged.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we used the latest version of the MAIAC AOD data (ftp://maiac@dataportal.nccs.nasa.gov/DataRelease/NorthAmerica_2000-2016/) from both Terra (overpass time at 10:30 am) and Aqua (overpass time at 1:30 pm) for April to September during 2011-2014. To improve the spatial coverage of the MAIAC AOD data, linear regression between daily Terra AOD and Aqua AOD were used to predict missing AOD when only one of them was available (X. F. Hu, Waller, Lyapustin, Wang, Al-Hamdan, et al, 2014;Jinnagara Puttaswamy et al, 2014). Then AOD data from both satellite were averaged.…”
Section: Maiac Aod Datamentioning
confidence: 99%
“…The other type of the AOD merging method are geostatistical methods, which include the universal kriging method [Chatterjee et al, 2010;Li et al, 2014], the geostatistical inverse modeling [Wang et al, 2013], and the spatial statistical data fusion (SSDF) method [Nguyen et al, 2012]. SSDF is a variant of kriging method specifically designed to optimally combine information from two or more massive data sets and has been used for multisensor AOD fusion [Nguyen et al, 2012;Puttaswamy et al, 2013]. The geostatistical fusion methods incorporate the spatial autocorrelation of the AODs into the fusion, so that they can estimate the AODs at the pixels where even both original AOD products are missing.…”
Section: Introductionmentioning
confidence: 99%